2021
DOI: 10.3390/antibiotics10060732
|View full text |Cite
|
Sign up to set email alerts
|

Development of Bisphosphonate-Conjugated Antibiotics to Overcome Pharmacodynamic Limitations of Local Therapy: Initial Results with Carbamate Linked Sitafloxacin and Tedizolid

Abstract: The use of local antibiotics to treat bone infections has been questioned due to a lack of clinical efficacy and emerging information about Staphylococcus aureus colonization of the osteocyte-lacuno canalicular network (OLCN). Here we propose bisphosphonate-conjugated antibiotics (BCA) using a “target and release” approach to deliver antibiotics to bone infection sites. A fluorescent bisphosphonate probe was used to demonstrate bone surface labeling adjacent to bacteria in a S. aureus infected mouse tibiae mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 51 publications
3
21
0
Order By: Relevance
“…This efficacy is hypothesized to be from the BCA killing of S. aureus biofilm bacteria within the OLCN, which is not achieved by sitafloxacin due to the aforementioned biodistribution limits. Additionally, since the nitrogen-containing bisphosphonates have great potency to inhibit osteoclasts, the bisphosphonates used as the bonetargeting component of BCA are designed to be innocuous or have minimal effects on bone cells (Adjei-Sowah et al, 2021), and the lack of efficacy of our "non-nitrogen-containing" bisphosphonate controls (HPHBP and HPBP) is consistent with our design and hypothesis. However, one unexplained finding in our study is that only HBCS reduces osteoclast number, and not BCS (Figure 3).…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…This efficacy is hypothesized to be from the BCA killing of S. aureus biofilm bacteria within the OLCN, which is not achieved by sitafloxacin due to the aforementioned biodistribution limits. Additionally, since the nitrogen-containing bisphosphonates have great potency to inhibit osteoclasts, the bisphosphonates used as the bonetargeting component of BCA are designed to be innocuous or have minimal effects on bone cells (Adjei-Sowah et al, 2021), and the lack of efficacy of our "non-nitrogen-containing" bisphosphonate controls (HPHBP and HPBP) is consistent with our design and hypothesis. However, one unexplained finding in our study is that only HBCS reduces osteoclast number, and not BCS (Figure 3).…”
Section: Discussionsupporting
confidence: 74%
“…Based on this, we aimed to create a bone-targeted antibiotic conjugate that could achieve sustained concentrations of a drug well above the MEC at the site of bone infection. In support of this concept, we recently demonstrated that systemic administration of a BP-conjugated fluorophore (AF647-ZOL) specifically labels the cortical surface of the bone in immediate proximity to S. aureus bacteria during chronic osteomyelitis (Adjei-Sowah et al, 2021). We were also encouraged by our initial success with BP-conjugated ciprofloxacin for the oral indication (Sedghizadeh et al, 2017).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…From a clinical point of view, the studies concerning the use of BPs in the treatment of some protozoal infections [48], in the modulation of the immune response [49], in the mechanisms of tissue repair [50], and generally in improving cell survival [51], could have a significant impact on the management of many diseases. Additionally, in the field of bone health, new research addressed the role of BPs as transporters of other pharmacological substances that would otherwise reach the bone tissue with difficulty and low doses [52][53][54][55].…”
Section: Bisphosphonates As Therapeutic Moleculesmentioning
confidence: 99%